Comparison of Immunoglobulin IgA Level in the Stimulated Saliva of Caries-Free and Caries-Active Children Aged 7-10 Years - Heba N. Yassin (College of Dentistry/ University of Baghdad, 2016)
Background: Salivary immunoglobulin IgA plays an essential role in the immune response against dental caries. This studywas conducted to compare the salivary IgA levels and flow rate of stimulated saliva in caries active and caries free children. Materials and methods: The present study included sixty healthy children age 7-10 yearswho were divided into two groups. They were caries free and caries active children (30 children in each group). Assessment and recording of caries - experience were through the application of Decayed, Missing and Filled Tooth Index (DMFT) and (dmft) index, for permanent and deciduous teeth respectively. After dental examination, stimulated saliva samples were collected from the subjects and performed under standard condition following instruction cited by Tenovuo and Lagerlof, and chemically analyzed for the detection of salivary immunoglobulin (IgA).In addition, salivary flow rate for the children were evaluated. Data was then statistically analyzed using SPSSversion 18. Results: Salivary IgA levels were significantly higher in caries free children than caries active children and the flow rate were lower in caries active children in both gender as compared to caries free children. Conclusions: Within the limitation of this study, it can be concluded that that the flow rate and salivary IgA levels of the whole stimulated saliva have some role in protection against dental caries.